Implanting Religious and Moral Values to Children in Kindergarten Inclusion - Annafi' Nurul ‘Ilmi Azizah; Dio Ardiansyah; Idha Aryani Febriana; Vema Nur Aliffah; Muhamad Bachrul Qolbi Khairudin (Journal of Islamic Education Students (JIES), 2024)
The aim this research is to find out the teacher's strategy in instilling religious andmoral values in the child. This research uses a type of descriptive qualitativeresearch with data collection techniques through observations, interviews anddocumentation. As for the respondents in this study, one head of school and twoteachers. The results show that the strategies used by teachers in cultivatingreligious and moral values are carried out through routineactivities to saygreetings and shaking hands, activities to play together with respect for each other,activities of worship dhuha every morning, activities giving to each other everyFriday, activities reading short surah and doing daily and sholawat, as well asactivities of eating together. In addition, children are taught tolerance or mutualrespect for religious differences.